Diagnostic guidlines for occupational epicondylitis - Patrycja Krawczyk-Szulc; Ewa Wągrowska-Koski; Anna Puzder; Przemysław Markowski; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2015)
Making final decisions on the occupational etiology of musculoskeletal diseases is often difficult and problematic at every stage of the diagnostic procedure. Taking into account the need to facilitate decision-making about the causal relationship between the diagnosed disease entity and the working conditions guidelines for the recognition of work-related musculoskeletal diseases have been developed. This paper presents the guidelines for the diagnosis of occupational etiology of humeral epicondylitis, one of the most common occupational disease of the musculoskeletal system in Poland. The developed guidelines have been based on the literature data concerning occupational risk factors of humeral epicondylitis, workload classification, including repetitive movements, awkward postures, and force. Some criteria applied in ergonomic evaluation methods were also included. The presented diagnostic guidelines define approximate benchmarks for stating (after excluding non-occupational etiology) that the identified humeral epicondylitis, is related to the way of working. Crucial work factors that should be analyzed include an operating time of movements overloading tendons connecting to the epicondyle, repetition and force used to perform occupational activities. The developed guidelines are aimed to facilitate occupational physicians diagnostic and certification procedures in case of humeral epicondylitis and determination whether there is a likelihood of its occupational etiology. Med Pr 2015;66(3):443-450